Genetic yield of next-generation sequencing for detecting monogenic familial hypercholesterolemia in uzbek patients with coronary artery disease - Rano B. Alieva; Aleksandr B. Shek; Anastasiya V. Bahachova; Khurshid G. Fozilov; Guzal J. Abdullaeva; Alisher A. Abdullaev; Lilya E. Kan; Shavkat U. Khoshimov; Andrey R. Kim; Ulugbek I. Nizamov; Dilnora B. Yusupalieva (PLoS ONE, 2026)
Background Familial hypercholesterolaemia (FH) is an inherited disorder with markedly elevated LDL-C and increased risk of premature atherosclerotic cardiovascular disease, most often caused by pathogenic variants in LDLR and less frequently APOB / PCSK9 (or recessive LDLRAP1 ). FH is commonly assessed using the Dutch Lipid Clinic Network (DLCN) score (definite >8, probable 6–8, possible 3–5). In Uzbekistan, genetic evidence for FH remains limited and largely based on candidate-variant studies, and the diagnostic yield of NGS for monogenic FH in CAD patients is not well defined. Aim For the first time in Uzbekistan and Central Asia, to investigate FH-associated monogenic variants using next-generation sequencing (NGS) and to assess the validity of the DLCN criteria against genetic testing as the diagnostic reference standard in Uzbek patients with CAD and suspected FH. Methods This study included 95 patients with coronary artery disease (CAD) who underwent targeted NGS of LDLR , APOB , PCSK9 , and LDLRAP1 . The suspected/phenotypic FH group comprised 56 patients: 53 with DLCN-predicted heterozygous FH (HeFH)—possible (3–5 points, n = 22), probable (6–8 points, n = 16), and definite (>8 points, n = 15)—and 3 siblings from one family with a homozygous FH (HoFH) phenotype. The control group included 39 CAD patients with hypercholesterolemia without an FH diagnosis (DLCN 1–2 points). Only pathogenic/likely pathogenic (P/LP) variants were used for genetic confirmation of FH. Results Pathogenic/likely pathogenic variants were detected in 10/53 (18.9%) DLCN-predicted HeFH patients and in all three HoFH siblings. Genetic confirmation rates (PPV) were 46.7% (7/15) in definite HeFH, 12.5% (2/16) in probable HeFH, and 4.5% (1/22) in possible HeFH; no P/LP variants were detected in controls (0/39). Using a DLCN >8 threshold, sensitivity was 70.0% (7/10) and specificity was 90.2% (74/82) in the CAD cohort excluding the HoFH family. Conclusion NGS confirmed the highest diagnostic yield in patients with DLCN >8, supporting its use as a practical threshold to prioritise genetic testing; however, monogenic FH may still be present in patients with probable or possible DLCN scores.